The impact of COVID-19 on tourism - Rita, Paulo (2022)
Rita, P., Moro, S., & Cavalcanti, G. (2022). The impact of COVID-19 on tourism: Analysis of online reviews in the airlines sector. Journal of Air Transport Management, 104(September), [102277]. https://doi.org/10.1016/j.jairtraman.2022.102277 -------- Funding Information: Paulo Rita was supported through the FCT (Fundação para a Ciência e a Tecnologia) under UIDB/04152/2020—Centro de Investigação em Gestão de Informação (MagIC)/NOVA IMS.